Analisis Pembinaan Prestasi Cabang Olahraga Sepak Bola di Sekolah Sepak Bola (SSB) Se-Kabupaten Pati - Mohammad Agil Ma'ruf; Mohamad Annas (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to find out how the development of football school achievement in the Pati district. The research method used in this research is descriptive qualitative. The object of this research is SSB Soegondo, SSB Bina Mandiri, SSB Basoka, SSB Regaloh and SSB Merpati Putra Karaban. The research data instrument was processed using the triangulation method. The results of the research conducted showed that, 1) Coaching includes the mass, nursery and achievement stages, 2) Recruitment of athletes without any special selection to join, 3) Recruitment of licensed training, 4) The training program implemented is good, namely there is physical exercise, mental training and technical training, 5) Completeness of facilities and infrastructure in good category but still need to be added to develop training, 6) Organization in SSB is structured and running smoothly, 7) Funding for SSB comes from the SSB student tuition. In conclusion, the SSB development process in the Pati Regency area has been going well, starting from student recruitment or holding tournaments, the existence of an organization, infrastructure, although it is not yet complete, but it is sufficient to carry out training and the achievements of several SSBs.